Practice makes perfect: Performance optimisation in 'arboreal' parkour athletes illuminates the evolutionary ecology of great ape anatomy. Issue 103 (February 2017) - Halsey, Lewis G.; Coward, Samuel R.L.; Crompton, Robin H.; Thorpe, Susannah K.S.
Abstract: An animal's size is central to its ecology, yet remarkably little is known about the selective pressures that drive this trait. A particularly compelling example is how ancestral apes evolved large body mass in such a physically and energetically challenging environment as the forest canopy, where weight-bearing branches and lianas are flexible, irregular and discontinuous, and the majority of preferred foods are situated on the most flexible branches at the periphery of tree crowns. To date the issue has been intractable due to a lack of relevant fossil material, the limited capacity of the fossil record to reconstruct an animal's behavioural ecology and the inability to measure energy consumption in freely moving apes. We studied the oxygen consumption of parkour athletes while they traversed an arboreal-like course as an elite model ape, to test the ecomorphological and behavioural mechanisms by which a large-bodied ape could optimize its energetic performance during tree-based locomotion. Our results show that familiarity with the arboreal-like course allowed the athletes to substantially reduce their energy expenditure. Furthermore, athletes with larger arm spans and shorter legs were particularly adept at finding energetic savings. Our results flesh out the scanty fossil record to offer evidence that long, strong arms, broad chests and a strong axial system, combined with the frequent use of uniform branch-to-branch arboreal pathways, were critical to off-setting the mechanical and energetic demands of large mass in ancestral apes.